2012
DOI: 10.21236/ada564982
|View full text |Cite
|
Sign up to set email alerts
|

2011 Center for Army Leadership Annual Survey of Army Leadership (CASAL): Army Civilian Leaders

Abstract: Public reporting burden for this collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing this collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing this burden to Department of Defense, Washington Headquarters Services, Directorate for Info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Practices that civilian leaders more often engaged in 'occasionally' or 'rarely' include self development (52%), learning from superiors (54%), formal leader development programs (60%), and developmental counseling from a supervisor (67%). Mentorship from someone outside the chain of command was reported to occur the least often (32% 'never' and 50% 'occasionally or rarely') (Riley, Conrad, & Keller-Glaze, 2012).…”
Section: Development Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Practices that civilian leaders more often engaged in 'occasionally' or 'rarely' include self development (52%), learning from superiors (54%), formal leader development programs (60%), and developmental counseling from a supervisor (67%). Mentorship from someone outside the chain of command was reported to occur the least often (32% 'never' and 50% 'occasionally or rarely') (Riley, Conrad, & Keller-Glaze, 2012).…”
Section: Development Methodsmentioning
confidence: 99%
“…Though it was not assessed in the 2012 CASAL, past studies have found that perceptions about organizational support for self-development vary. In 2011, just over one-third (38%) of civilian leaders agreed their unit or organization made time available for self development, though more than half (55%) believed their organization expected them to participate in self development other than mandatory training (Riley, Conrad, & Keller-Glaze, 2012).…”
Section: Self Developmentmentioning
confidence: 99%